Multiparametric Cardiovascular Magnetic Resonance in Acute Myocarditis: Comparison of 2009 and 2018 Lake Louise Criteria With Endomyocardial Biopsy Confirmation - Li, Shuang; Duan, Xuejing; Feng, Guangxun; Sirajuddin, Arlene; Yin, Gang; Zhuang, Baiyan; He, Jian; Xu, Jing; Yang, Wenjing; Wu, Weichun; Sun, Xiaoxin; Zhao, Shihua; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background Cardiac magnetic resonance (CMR) has been shown to improve the diagnosis of myocarditis, but no systematic comparison of this technique is currently available. The purpose of this study was to compare the 2009 and 2018 Lake Louise Criteria (LLC) for the diagnosis of acute myocarditis using 3.0 T MRI with endomyocardial biopsy (EMB) as a reference and to provide the cutoff values for multiparametric CMR techniques. Methods A total of 73 patients (32 ± 14 years, 71.2% men) with clinically suspected myocarditis undergoing EMB and CMR with 3.0 T were enrolled in the study. Patients were divided into two groups according to EMB results (EMB-positive and -negative groups). The CMR protocol consisted of cine-SSFP, T2 STIR, T2 mapping, early and late gadolinium enhancement (EGE, LGE), and pre- and post-contrast T1 mapping. Their potential diagnostic ability was assessed with receiver operating characteristic curves. Results The myocardial T1 and T2 relaxation times were significantly higher in the EMB-positive group than in the EMB-negative group. Optimal cutoff values were 1228 ms for T1 relaxation times and 58.5 ms for T2 relaxation times with sensitivities of 86.0% and 83.7% and specificities of 93.3% and 93.3%, respectively. The 2018 LLC had a better diagnostic performance than the 2009 LLC in terms of sensitivity, specificity, positive predictive value, and negative predictive value. T1 mapping+T2 mapping had the largest area under the curve (0.95) compared to other single or combined parameters (2018 LLC: 0.91; 2009 LLC: 0.76; T2 ratio: 0.71; EGEr: 0.67; LGE: 0.73; 2018 LLC+EGEr: 0.91; and T2 ratio+LGE: 0.76). The diagnostic accuracy for the 2018 LLC was the highest (91.8%), followed by T1 mapping (89.0%) and T2 mapping (87.7%). Conclusions Emerging technologies such as T1/ T2 mapping have significantly improved the diagnostic performance of CMR for the diagnosis of acute myocarditis. The 2018 LLC provided the overall best diagnostic performance in acute myocarditis compared to other single standard CMR parameters or combined parameters. There was no significant gain when 2018LLC is combined with the EGE sequence.